Testing the employment and skill impact of new technologies: A survey and some methodological issues - Laura Barbieri; Chiara Mussida; Mariacristina Piva; Marco Vivarelli (Global Labor Organization (GLO), 2019)
The present technological revolution, characterized by the pervasive and growing presence of robots, automation, Artificial Intelligence and machine learning, is going to transform societies and economic systems. However, this is not the first technological revolution humankind has been facing, but it is probably the very first one with such an accelerated diffusion pace involving all the industrial sectors. Studying its mechanisms and consequences (will the world turn into a jobless society or not?), mainly considering the labor market dynamics, is a crucial matter. This paper aims at providing an updated picture of main empirical evidence on the relationship between new technologies and employment both in terms of overall consequences on the number of employees, tasks required, and wage/inequality effect.
Keywords: O33; 330; technology; innovation; employment; skill; task; routine